1999
DOI: 10.1088/0953-8984/11/11/013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a strong magnetic field on the binding energy and the photoionization cross-section in a quantum well

Abstract: The effect of a strong magnetic field on the binding energy and the photon energy dependence of the photoionization cross-section as a function of the well size is studied in a quantum well for several values of the magnetic field, taking into account the finite character of the barrier potential. The results we have obtained show that the applied strong magnetic field affects drastically the binding energy and the photoionization cross-section and this effect is more significant in a quasi-two-dimensional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…It is important to mention that the increasing electronic confinement achieved by the reduction of the dimensionality by going from the three-dimensional system [66] to the quantum dot structures, going by way of the quantum well [54,57] and quantum-well wire [58,60] systems with small dimensions, causes the magnitude of the cross-section to become smaller and the peak of the cross-section to move towards the photoionization threshold energy. The peak at small photon energies is coming from the localization of the electronic wavefunction near the edge of the small systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to mention that the increasing electronic confinement achieved by the reduction of the dimensionality by going from the three-dimensional system [66] to the quantum dot structures, going by way of the quantum well [54,57] and quantum-well wire [58,60] systems with small dimensions, causes the magnitude of the cross-section to become smaller and the peak of the cross-section to move towards the photoionization threshold energy. The peak at small photon energies is coming from the localization of the electronic wavefunction near the edge of the small systems.…”
Section: Resultsmentioning
confidence: 99%
“…The photon energy dependence of the photoionization cross-section in low-dimensional electronic systems is generally determined by the impurity ground state wavefunction, the potential which links the electron to the donor impurity and the conduction subband of the host crystal and by the wavefunction of the conduction subbands into which the charge carrier is excited. Recently, much attention has been devoted to the study of the hydrogenic impurity photoionization cross-section in systems with reduced dimensionality such as quantum wells [53][54][55][56][57][58] and quantum-well wires [59][60][61]. Most of these works can be summarized as follows: Takikawa et al [53] have experimentally and theoretically examined the photoionization of the deep traps in AlGaAs/GaAs multiple quantum well layers grown by metalorganic chemical vapour deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lax [1] first investigated the photoionization cross-section of hydrogenic impurities in bulk semiconductors. In recent years, work has been done on the photoionization crosssection of hydrogenic impurities in dimensionally reduced structures such as quantum wells, wires and quantum dots [2][3][4][5][6][7][8][9][10]. It has been found that greater the confinement in such low-dimensional structures, greater the binding energy of these hydrogenic impurities.…”
Section: Introductionmentioning
confidence: 99%
“…Jayam and Navaneethakrishnan [6] have calculated the photoionization cross-section of donor impurities in quantum wells in an electric field. Recently Sali et al [7,8] have investigated the photoionization cross-section of impurities in quantum-well wires and quantum dots. Recently, Sali et al [9] have investigated the influence of a strong magnetic field on the ground state binding and photon energy dependence of the photoionization cross-section of a shallow donor impurity in a quasi-one-dimensional rectangular quantum wire with infinite and finite potential barriers using a variational approach.…”
Section: Introductionmentioning
confidence: 99%